CHA2DS2-VASc score for in-hospital recurrence risk stratification in patients with myocardial infarction - Pang, Hui; Zhu, Xu; Cheang, Iokfai; Zhang, Haifeng; Zhou, Yanli; Liao, Shengen; Li, Xinli (Frontiers in Cardiovascular Medicine, 2022)
Backgroud: Using CHA2DS2-VASc score to recognize the risk of stroke in patients with atrial fibrillation has been well established. However, few studies have assessed whether CHA2DS2-VASc score has been similar predictive value in recurrence after myocardial infarction (MI). Methods: We conducted a retrospective observational cohort study of adult inpatients with MI. The CHA2DS2-VASc and modified CHA2DS2-VASc (MCHA2DS2-VASc) scores of all patients were calculated. The associations of both scores with recurrent MI were analyzed. Results: A total of 6700 MI patients (60.0 ± 11.1 years, 77.2% men) were enrolled and 759 (11.3%) presented a definite recurrence during hospitalization. After multivariable adjustment by logistic regression in patients with MI, the CHA2DS2-VASc and MCHA2DS2-VASc scores were independently associated with recurrence. MCHA2DS2-VASc score showed better predictive value for risk of recurrence than that of CHA2DS2-VASc in overall [area under the receiver operating characteristic curve (AUC) 0.757 vs. 0.676], or men patients (AUC 0.759 vs. 0.708). MCHA2DS2-VASc was superior to CHA2DS2-VASc for identifying ‘truly high-risk’ patients with MI, regardless of overall patients or sex-specific subgroups. The two scores had similar focus on identification of ‘low-risk’ patients in overall or women, but not in men. Conclusions: The CHA2DS2-VASc and MCHA2DS2-VASc scores for predicting recurrence are validated in patients with MI. However, MCHA2DS2-VASc could be more helpful to the secondary prevention than CHA2DS2-VASc after MI, especially in men. The superiority of MCHA2DS2-VASc compared to CHA2DS2-VASc in women is just more discriminatory for ‘truly high-risk’ patients.